A Brief Review on Deep Learning Applications in Genomic Studies - Shen, Xiaoxi; Jiang, Chang; Wen, Yalu; Li, Chenxi; Lu, Qing (Frontiers in Systems Biology, 2022)
Deep learning is a powerful tool for capturing complex structures within the data. It holds great promise for genomic research due to its capacity of learning complex features in genomic data. In this paper, we provide a brief review on deep learning techniques and various applications of deep learning to genomic studies. We also briefly mention current challenges and future perspectives on using emerging deep learning techniques for ongoing and future genomic research.